2023
DOI: 10.3390/vaccines11030630
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the Past to Improve the Future—Vaccine Hesitancy Determinants in the Italian Population: A Systematic Review

Abstract: WHO identifies vaccine hesitancy (VH) as one of the ten threats to global health. The authors bring to the international scientific community an Italian episode that offers the opportunity to renew the discussion on the extent of the VH matter. The purpose of this systematic review is to analyze the factors determining vaccine hesitancy in the Italian population, to understand its roots, and suggest potential strategies to mitigate it. A systematic review of the literature according to the PRISMA guidelines wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…A larger sample size might yield significant results. Similar findings concerning distrust in institutions, the government, public health authorities, and in the information received were reported in various studies on the willingness to get vaccinated [ 40 , 41 , 42 , 43 , 44 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A larger sample size might yield significant results. Similar findings concerning distrust in institutions, the government, public health authorities, and in the information received were reported in various studies on the willingness to get vaccinated [ 40 , 41 , 42 , 43 , 44 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 83%
“…A multivariate analysis revealed that sociodemographic factors influenced vaccination propensity; notably, there was a (female) gender-related refusal of the COVID-19 vaccination among the foreign resident group, unlike the Italian group. No significant association was reported in scientific literature between gender and migrants’ willingness to get vaccinated [ 40 , 41 , 42 ], while two systematic reviews reported that the female gender is a determinant for hesitancy in the Italian population [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between sex, age and uptake of vaccination can be discussed in the light of current knowledge on the factors influencing vaccine hesitancy. In fact, two systematic reviews on COVID-19 vaccination hesitancy in the Italian population reported a higher hesitancy in females and younger people [ 18 , 30 ]. These results were also confirmed by studies performed outside Italy and their systematic reviews [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A novel coccidioidal vaccine will require a specific plan to educate the public about its benefits and potential risks. This will require a multipronged approach directed at education from trusted sources, examination of social and cultural values, and retooling of health-related media platforms to combat misinformation [ 79 ]. In addition, the populations initially targeted for vaccination should be those who are most at risk and would most benefit from vaccination.…”
Section: Four Questions For the Development Of A Coccidioidal Vaccinementioning
confidence: 99%